Development and acceptance of polyherbal formulation for memory enhancement - Zainol Abidin, Nurul Alyani; Kormin, Faridah; Mat Salleh, Nurul Shafira; Mohamed Anuar, Nor Aini Fatihah (Medwell Publishers, 2018)
Simplex-centroid mixture design has been applied to investigate the acceptance on the polyherbal formulation for memory enhancement. Polyherbal formulation consists of three different herbs (Centella asiatica, Piper sarmentosum and Morinda citrifolia) as independent variables and mixed with honey bee (Apis cerana) as the medium was developed. Consumer acceptability was measured in terms of nine dependent variables by 50 semi-trained panelists using a 9-point hedonic scale. Results showed that overall acceptability was affected mostly by changes in the interaction of Centella asiatica and Piper sarmentosum, Centella asiatica and Morinda citrifolia, Piper sarmentosum and Morinda citrifolia (p<0.05). Optimization suggested a polyherbal formulation containing Centella asiatica only as the best proportion of these mixtures.